Protective effect of epigenetic silencing of CyclinD1 against spinal cord injury using bone marrow‐derived mesenchymal stem cells in rats. Issue 7 (23rd January 2018) - Wang, Yuan; Kong, Qing‐Jie; Sun, Jin‐Chuan; Xu, Xi‐Ming; Yang, Yong; Liu, Ning; Shi, Jian‐Gang
Abstract : This study focuses on the protective effect of epigenetic silencing of CyclinD1 against spinal cord injury (SCI) using bone marrow‐derived mesenchymal stem cells (BMSCs) in rats. Eighty‐eight adult female Wistar rats were randomly assigned into the sham group, the control group, the si‐CyclinD1 + BMSCs group and the BMSCs group. CyclinD1 protein and mRNA expressions after siRNA transfection were detected by Western blotting and qRT‐PCR. The siRNA‐CyclinD1 BMSCs were transplanted into rats in the si‐CyclinD1 + BMSCs group using stereotaxic method 6 hr after SCI. Hindlimb locomotor performance was determined using inclined plane test and Basso‐Beattie‐Bresnahan (BBB) locomotor rating scale. Expressions of glial fibrillary acidic protein (GFAP) and nerve growth factor (NGF) were detected by immunohistochemistry. Inclined plane and BBB scores in the control, si‐CyclinD1 + BMSCs, and BMSCs groups were significantly lower than the sham group, but these scores were evidently decreased in the control group and increased in the si‐CyclinD1 + BMSCs group compared with the BMSCs group. The repair degree of spinal cord tissues of rats in the si‐CyclinD1 + BMSCs group was obvious than the BMSCs group. GFAP and NGF protein expressions were markedly decreased in the control, si‐CyclinD1 + BMSCs and BMSCs groups when compared with the sham group. GFAP‐ and NGF‐positive cells were significantly increased in the si‐CyclinD1 + BMSCs group while decreased in the control group. Our study provides evidence that epigenetic silencing of CyclinD1 using BMSCs might accelerate the repair of SCI in rats. Abstract : Our study provides evidence that epigenetic silencing of CyclinD1 using BMSCs might accelerate the repair of SCI in rats.